Christus Redemptor : an outline study of the island world of the Pacific / by Helen Barrett Montgomery. - Montgomery, Helen Barrett, 1861-1934. (Tufts University. Tisch Library., 2015)
New edition, revised.; 1 online resource (viii, 292 pages) : map; First edition 1906.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.